Saraswati Nakhva from Mazagaon Koliwada - Mumbai Archive Project Team (Jio Institute, 2024)
Saraswati Narsu Nakhva, 85, resides in her ancestral home built by her father in Mazagaon Koliwada. She led an active life as a fisherwoman until retiring at 80 due to the severe impact of COVID-19 on her business.